Hands over the city = Le mani sulla città - Piccioni, Piero 1921-2004 (Eureka, 2014)
The structure of power and the facade of democracy are explored in this political exposé of corruption in Naples. Following the fatal collapse of a tenement building, an investigation reveals that profits from municipal developments are going to city council members and developers in backroom negotiations.
Bildformat 1.85:1
Orig.: Italien, Frankreich, 1963
Enth. new video interviews with Rosi, film critic Tullio Kezich and filmmaker Jean-Pierre Gorin ; video discussion with Rosi, co-writer Raffaele La Capria and film critic Michel Ciment
Keywords: Geschichte 1900-2000; Politik; Feature films; Fiction films; Foreign films; Housing developers -- Drama; Melodrama; Motion pictures, Italian; Political corruption -- Drama; Real estate development -- Drama; Italië; Naples (Italy) -- Drama; Naples (Italy) -- Politics and government -- 20th century -- Drama; Melodrama - Feature